Employment status five years after a randomised controlled trial comparing multidisciplinary and brief intervention in employees on sick leave due to low back pain. Issue 3 (May 2018) - Pedersen, Pernille; Nielsen, Claus Vinther; Jensen, Ole Kudsk; Jensen, Chris; Labriola, Merete
Aims: To evaluate differences in employment status, during a five-year follow-up period in patients on sick leave due to low back pain who had participated in a trial comparing a brief and a multidisciplinary intervention. Methods: From 2004 to 2008, 535 patients were referred to the Spine Centre at the Regional Hospital in Silkeborg if they had been on sick leave for 3–16 weeks due to low back pain. All patients underwent a clinical examination by a rehabilitation physician and a physiotherapist, and were randomised to either the brief intervention or the multidisciplinary intervention. The outcome was employment status from randomisation to five years of follow-up and was measured by the mean number of weeks in four different groups of employment status (sequence analysis) and a fraction of the number of weeks working (work participation score) that were accumulated over the years. Results: A total of 231 patients were randomised to the brief intervention and 233 patients to the multidisciplinary intervention. No statistically significant differences in the mean weeks spent within the different employment statuses were found between the two intervention groups. After five years of follow-up, participants in the multidisciplinary intervention had a 19% higher risk of not having a work participation score above 75% compared to participants in the brief intervention. Conclusions: After five years of follow-up no differences in employment status were found between participants in the brief and the multidisciplinary intervention.